1999
DOI: 10.1097/00000658-199902000-00013
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR Expression and Soluble HLA-DR Levels in Septic Patients After Trauma

Abstract: In severely injured patients, decreased levels of cellular and soluble HLA-DR appear as early indicators of an immune deviation associated with the development of severe sepsis. Moreover, immune alterations of different cell types may promote distinct kinds of septicemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
3
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(119 citation statements)
references
References 44 publications
8
104
3
4
Order By: Relevance
“…8 Current results dovetail with a large body of work implicating a critical role of monocyte subsets and dendritic cells in the immune response to traumatic injury and surgical recovery. [20][21][22][23][24][25][26][27] The findings integrate with the well-established role of the TLR4 signaling pathway in the innate immune response to traumatic injury. 28 MAPKAPK2 is a component of the p38 MAP kinase pathway, which mediates TLR4 priming in injury.…”
Section: Discussionsupporting
confidence: 70%
“…8 Current results dovetail with a large body of work implicating a critical role of monocyte subsets and dendritic cells in the immune response to traumatic injury and surgical recovery. [20][21][22][23][24][25][26][27] The findings integrate with the well-established role of the TLR4 signaling pathway in the innate immune response to traumatic injury. 28 MAPKAPK2 is a component of the p38 MAP kinase pathway, which mediates TLR4 priming in injury.…”
Section: Discussionsupporting
confidence: 70%
“…On admission the mean age of the trauma patients ( n = 31) was 32·8 (range, 18-59), the mean ISS was 32·0 (17-59), APACHE II score of 13·5 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and mean GCS of 8·7 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). There were 25 men and six women.…”
Section: Resultsmentioning
confidence: 99%
“…1 day after the traumatic event, was evaluated by assessment of HLA-DR expression on monocytes, a parameter known to correlate with clinical outcome in diverse populations [7][8][9][10][11][12]. In addition, the proliferative capacity of T cells and cytokine production profile upon mitogenic stimulation were evaluated, because T cells are essential for a primary immune response and were reported to be functionally compromised in traumatized patients [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the decrease of mHLA-DR expression has mainly been assessed as a predictor of septic complications after trauma, surgery, or pancreatitis (28,(92)(93)(94)(95)(96)(97)(98). In these studies, low levels of mHLA-DR (<40% of positive monocytes, normal >90%) were observed in patients who subsequently developed nosocomial infections.…”
Section: Mhla-dr Expression and Clinical Studymentioning
confidence: 99%